Logbook Quality Analysis at PT. Pertamina Patra Niaga Ships Using Sus and Webqual 4.0 Methods - Muhamad Fitra Saputra; Budi Setiawan; Sartika Rini (Jurnal Sosial Teknologi, 2026)
The APLUSAN website is a website-based application used by PT. Pertamina Patra Niaga - SHIPS workers are responsible for reporting shift handover logbooks. User satisfaction and usability testing has not occurred since the APLUSAN website was implemented. The aim of this research is analyzing the website using the Webqual 4.0 method to assess the quality of the website and the System Usability Scale (SUS) method to measure website usability at a superficial level. Researchers collected data through literature studies, observations, and questionnaires using the Saturated Sampling technique. The subjects of this study were 30 respondents from PT. Pertamina Patra Niaga - SHIPS Refueling and Operational Head division (N = 30). This study adapts quantitative analysis, including validity and reliability tests, with SPSS calculation tools. The results of the APLUSAN website increased quality, cost, delivery, safety, and morale, and also the satisfaction measurement of Webqual 4.0 indicates good quality and the System Usability Scale (SUS) method, with a score of 75.1, indicates could be accepted by PT. Pertamina Patra Niaga- SHIPS workers. Using SPSS 22 the validity & reliability test results show that all questionnaire items are valid and reliable. The APLUSAN Website has the potential for replication and could be applied in all PT. Pertamina Patra Niaga work locations. Sustainable use requires enhancing service quality based on the company's demands. Data protection against data theft must be improved, servers should be added to accommodate growing user numbers, and this website must stay current on technological advances to be relevant.